Adolescent Pregnancy in Bangladesh: Understanding Care-Seeking Behaviour and Practices to Advance Responsive Antenatal Care and Nutrition Services - Busch-Hallen, Jennifer (Curr Dev Nutr, 2021)
OBJECTIVES: Compared to pregnant women, pregnant adolescents in Bangladesh are less likely to utilize maternal health services. The objective of this study was to explore their experiences of seeking, accessing, and navigating antenatal care (ANC) and nutrition services in Bangladesh. METHODS: Peer-interviewers (age 17–20 yrs) in Dhaka and Rangpur obtained informed consent and interviewed respondents (n = 192): adolescents who were pregnant or had a child under 1 year, family members, and healthcare providers. Questions explored barriers and enablers to ANC access, interactions with the healthcare system, micronutrient supplementation, dietary practices, nutrition advice given by healthcare providers, and adolescents’ agency and decision-making. Qualitative research methods were used: transcripts were anonymized, coded (ensuring intercoder reliability), and analyzed thematically. RESULTS: Respondents felt that adolescent childbearing was risky and additional support was required. Cost was perceived as the greatest barrier to nutrition and healthcare including supplements, ultrasounds, and facility-based care, despite some availability of subsidized or free services. Pregnant adolescents were accompanied by family members to health facilities, sometimes only seeking care for emergencies. Nutrition advice given by healthcare providers did not always align with traditional practices, although they were a trusted source of medical information. Supplements were mostly received after first trimester. Some pregnant adolescents reported receiving generic nutrition advice from healthcare providers but seldom had a chance to ask questions and felt a lack of respect. Quality of care was perceived to vary widely from one healthcare provider to the next. CONCLUSIONS: This study provides unique insights into the experience of pregnant adolescents in Bangladesh and their interface with the healthcare system, laying a foundation for tailoring nutrition and ANC guidelines specifically for them. As experiences were influenced by social norms, limited agency, and family decision-making, healthcare providers should be equipped with behavior change communication skills specifically for pregnant adolescents to ensure they receive quality gender-responsive, youth-friendly health and nutrition services. FUNDING SOURCES: Global Affairs Canada.